The Effect of Enterprise Risk Management, Firm Size, Profitability, Leverage, and Managerial Ownership on Firm Value - Nur Halimah, Sundus; Kristianti Maharani, Novera (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2024)
The phenomenon of a Tobin's q value of less than 1 indicates a decrease in firm value. Knowing the effect of ERM (Enterprise Risk Management), firm size as proxied by ln (total assets), profitability as proxied by return on assets, leverage as proxied by debt to equity ratio, and managerial ownership on firm value by Tobin's q in conventional commercial banks listed on the IDX in 2017-2022 is the aim of the study. Quantitative methods used in this study and data analysis using SPSS 26. The number of samples is 84 data. Firm value impacted simultaneous by ERM, firm size, profitability, leverage, managerial ownership. In the partial test, firm value have no impacted by ERM and managerial ownership, the firm value has a significant negative impacted by firm size, while the firm value show results that have a significant positive impacted by profitability and leverage variables. Other variables can be added in further study such as bank health calculation ratios, including non-performing loans, so that you can get a regression model with high value.